Incidence of osmophilic yeasts and Zygosaccharomyces rouxii during the production of concentrate grape juices - Torres Palazzolo, C.; Cuello, Raúl Andrés; Gonzalez, Magali Lucia Rosa; Guevara, Felipe; Ponsone, María Lorena; Mercado, Laura Analia; Martinez, Claudio; Combina, Mariana; Rojo, Maria Cecilia (2017)
Zygosaccharomyces rouxii is the main spoilage yeast of grape juice concentrates. Detection and identification of Z. rouxii during the production of grape juice concentrate is critical to prevent spoilage in the final product. In this work, three grape juice concentrate processing plants were assessed by identifying osmophilic yeasts in juices and surfaces during different stages of a complete production line. Subsequently, molecular typing of Z. rouxii isolates was done to determine the strain distribution of this spoilage yeast. Osmotolerant yeast species, other than Z. rouxii, were mainly recovered from processing plant environments. Z. rouxii was only isolated from surface samples with grape juice remains. Z. rouxii was largely isolated from grape juice samples with some degree of concentration. Storage of grape juice pre-concentrate and concentrate allowed an increase in the Z. rouxii population. A widely distributed dominant molecular Z. rouxii pattern was found in samples from all three processing plants, suggesting resident microbes inside the plant